Pengaruh pH ekstraksi pada pewarnaan batik sutera menggunakan pewarna alami kulit kayu mahoni (Switenia mahagoni) - Dwi Wiji Lestari; Vivin Atika; Agus Haerudin; Tin Kusuma Arta (Jurnal Rekayasa Proses, 2020)
The natural dye extracted from Swietenia mahagoni was applied to silk batik. Mahagoni bark is known to contain dyestuff components such as flavonoids and tannins. The dye compound was extracted using water at pH values of 6 (original pH extract), pH 2 (acid), and pH 12 (base) at 100 °C for 1 hour. Variation of extraction pH values was carried out to determine the influence of temperature on the results of the extract. Batik dyeing was carried out at room temperature using dye products. The pre-mordanting and post-mordanting used were alum (Al2(SO4)3.K2SO4.24H2O). The results showed that the dye product extracted in alkaline pH shows a high amount of tannins and flavonoids and the ability to color the silk batik better. The color direction is reddish-brown. The pH values of extraction do not affect the results of the colorfastness to washing test, which is on 4-5 (good) scale.